Prevalence of Psychosocial Problems of Computer Users in Abadan Oil Company - Arqavan Afra, (Corresponding author); Heidar Aliabadi; hamid hojati; Sheida Rafizadeh (Iranian Association of Health Education and Health Promotion, 2013)
Background: Nowadays computer has changed to an integral component in all the workplaces particularly in administrative ones. Health is directly related to internalsocial factors of work.Objective: This research is conducted to determine the Prevalence of psychosocial complications among computer users and to specify the factors influencing these complications. Method: The method of the present study is correlational and it is conducted randomly on 199 computer users in Abadan oil company. The data were collected through demographic questionnaire and psychosocial complications resulting from using computers were assessed. The maintained information was analyzed through Spss-19. Results: The sample compromised 78 females and 121 males aged between 30- 40 averagely, who were using computers 21 to 40 hours on average in one week. The results indicated that 51.8% of participants were suffering from psychosocial complications due to using computers moderately and 3.1% of them with the minimum frequency faced severe complications. Significant statistical relationships were seen between these complications and working hours, working hours and computer, rest and education. Conclusion: At the present time the existence of psychosocial complications are not damaging in the society which is being investigated however, the users who use computer moderately are in danger and the way they use computers determines whether in future computer users will be addicted to computers severely or will be healthy users.